HUBUNGAN HARGA DIRI DENGAN PERILAKU KONSUMTIF REMAJA DI BANDA ACEH - Jasmadi Jasmadi; Aulia Azzama (Psikoislamedia : Jurnal Psikologi, 2016)
Some adolescence among at Banda Aceh could not to accept their physical self either excess or a deficiency in themself so that the adolescence doing the imitating behavior others people as a model (the idol) with consumptive behavior a manner in order to change the appearance for the sake of to cover their a deficiency. This objective research is to know the relationship between self esteem and consumptive behavior on adolescence at Banda Aceh and the hypothesis presented in this objective research are there is a negative relationship between self esteem and consumptive behavior on adolescence at Banda Aceh. The sample in this objective research involving 84 adolescence and sampling design by using simple random sampling. Data collected by using psychology scales is Self Esteem Scales compiled with reference to the Coopersmith theory (1967) and Consumptive Behavior Scales compiled with reference to the Sumartono theory (2002). Data to analys by using Product Moment correlation technique with correlation coefisient (r) was -0,324 and significant value (p) was 0,003 (p